If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 5 = 11x Reorder the terms: 5 + 16x = 11x Solving 5 + 16x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + 16x + -11x = 11x + -11x Combine like terms: 16x + -11x = 5x 5 + 5x = 11x + -11x Combine like terms: 11x + -11x = 0 5 + 5x = 0 Add '-5' to each side of the equation. 5 + -5 + 5x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = 0 + -5 5x = 0 + -5 Combine like terms: 0 + -5 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| (y^2)-18y+35=0 | | 2x+1+6=3x | | 2x+x*3=120 | | (x^2)-18x+35=0 | | -9n^2-6n-1=0 | | 5(x+8)-(x+8)=80 | | 14+30d=-196 | | -25x-75y+150=0 | | 30d+14=-196 | | y=2X^2-13X-7 | | -15x^2-40x=20x^2-8x | | 4f+g=25 | | 4(-6)+6(-512)= | | 5f+g=30 | | -3(2x-5)=51 | | 2x+14=x+1 | | 4(-6)+6(-8)= | | 4+8+9+3*5+7= | | -4p^2-4p-1=0 | | 7-5+3-2*9-4= | | y=1+0 | | y=200x+13176 | | 4-(-7y)=13-6y | | y=7-(1/2)14 | | 12*(12*9)*11= | | -9.3=y+7.7 | | p-4-(2p-5)=4+2(p+3) | | -4y-3x=7 | | c(x+a)=a(a+b) | | 7x+9y=-41 | | 0=7-(1/2)x | | y=7-(1/2)0 |